2017
DOI: 10.15537/smj.2017.1.16218
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender and age on forensic personal identification from frontal sinus in a Turkish population

Abstract: Objectives:To define the dimensions of the frontal sinus in groups standardized for age and gender and to discuss the reasons and the effects of the variations.Methods:Frontal sinus measurements were obtained from paranasal CT scans of 180 males and 180 females in the Radiology Department of Dursun Odabas Medical Center of Yuzuncu Yil University, Van, which is located in Eastern Turkey, between February and March 2016. The width and height of sinuses were measured on a coronal plane, and the anteroposterior le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
25
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 20 publications
8
25
0
11
Order By: Relevance
“…This is similar to other reports [5,10,[23][24][25][26][27][28] but contrary to study by Ariji et al which reported no significant difference between the genders [21]. Our study shows that generally, the left FS has higher dimensions than the right which is similar to other reports [29][30][31][32], but in contrast to another study done in India in which the right FS has higher values [27]. Furthermore, this study shows a positive correlation between left FS height and age.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to other reports [5,10,[23][24][25][26][27][28] but contrary to study by Ariji et al which reported no significant difference between the genders [21]. Our study shows that generally, the left FS has higher dimensions than the right which is similar to other reports [29][30][31][32], but in contrast to another study done in India in which the right FS has higher values [27]. Furthermore, this study shows a positive correlation between left FS height and age.…”
Section: Discussionsupporting
confidence: 91%
“…20 A recent study from the same group reported that FS size in females increased with age, whereas FS size in males decreased after the age of 50 years. 36 Regardless of age and gender, we found that FS morphology does not progress in the same direction as craniofacial structure development.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the age of the sample was also a determining factor for effective identification, since the final configuration of the frontal sinuses is only reached after the age of 20. 20 However, Tatlisumak et al 29 explored the pattern of frontal sinus configuration according to age, based on the belief that the frontal sinuses continue to expand to a later age, due to other factors and the influence of mechanical chewing factors. 32 In this case, it was agreed that there is a decrease in the frontal sinus area from the age of 70 years old, 29 but from the analysis performed, it was observed that the authors concluded that new studies need to be performed with less limited samples and looking at different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the type of image exam selected, it was verified that more than half of the studies used PA (posteroanterior) radiography. [14][15][16][17]19,20,22,[26][27][28][29][30] Thus, it was noted that conventional extraoral radiography is still the most viable and most used in the research, also emphasizing the increasing use, but still at a smaller scale, of threedimensional imaging resources, such as concomitant computed tomography. 10,13,18 In relation to the methodologies and identification parameters of the frontal sinus, the largest number of analyzes used both quantitative and morphological parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation